Pengaruh Diet Tinggi Serat Pangan terhadap Absorpsi Fe dan Efisiensi Regenerasi Hb Rattus norvegicus - Leny Yuanita (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2005)
The aim of the study were to find: 1)The effect of high intakes of dietary fiber on iron absorption and haemoglobin regeneration efficiency percentages, through combination of pH 4 and 7 with length of boiling time of 0 (raw), 5, 15, and 25 minutes. 2)The role of iron binding to dietary fiber on haemoglobin regeneration efficiency. The experiment involved yard long beans and 110 of male Rattus norvegicus (Wistar strains) as dietary fiber sources and animal model respectively. The results revealed that: 1) High intakes of yard long bean fiber will decreased iron absorption and haemoglobin regeneration efficiency. pH, boiling time and its interaction affected on iron absorption and haemoglobin regeneration efficiency (p < 0,05). On dietary fiber treatment, the highest iron absorption and haemoglobin regeneration efficiency at raw- pH 4 were higher than standard feeding treatment; while the lowest at pH 7- boiling time 5 minutes treatment. The treatment’s results at raw-pH 7 and pH4- boiling time 25 minutes were identical with standard feeding treatment. 2) An increase and decrease of boiling time and pH respectively increased iron absorption and haemoglobin regeneration efficiency, due to a decrease of iron binding to dietary fiber. The same results also occurred with non boiling treatment (raw condition) due to the role of exhancer substances on iron non heme absorption.